PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 S.D 2014 - Astutik, Sri; ', Makhdalena; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of cash turnover, accounts receivable turnover and inventory turnover, both simultaneously and partially on the profitability of the Consumer Goods companies listed in Indonesian Stock Exchange period 2010 to 2014. The total number of listed compaies in the Consumer Goods sub-sector is 38 companies. Consumer Goods companies population who have the necessary data in this study is 13 companies. . Data analysis techniques used in this research is multiple linear regression analysis. The result showed that the cash turnover, accounts receivable turnover and inventory turnover simultaneously affect the profitability of the company amounted to 13.6%. Further research showed that the effect of the partial cash turnover on the profitability of 0.073%, the effect on profitability piutan turnover amounted to 14.36%, and the effect of inventory turnover to profitability by 0.86%.Key Words: Profitability, Cash Turnover, Receivable Turnover, Inventory Turnover.